Implementasi Prinsip-Prinsip Ekonomi Islam Dalam Kemandirian Ekonomi Pesantren - Imam Suyuthi; Didin Hafidhuddin; Qurroh Ayuniyyah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Independence is not depending on others, both in terms of actions and economics. Pesantren is the oldest ancestral heritage and is a place for cadre of leaders. As KH. Hasyim Asy'ary, KH. Wahab Hazbollah, KH. Saifuddin Zuhri, KH. A. Wahid Hasyim and other Kyai who made extraordinary contributions to the Indonesian nation. So that the pesantren is not only equipped with knowledge about the afterlife, but is also balanced with the provision of world knowledge. The formulation of the problem in this research is how to apply the principles of Islamic economics (qowaid fiqhiyyah and its SWOT analysis in achieving the economic independence of Islamic boarding schools at Nur El Falah Islamic Boarding School Serang Banten and Fathul Ulum Islamic Boarding School Kwagean? The research method in this thesis is a qualitative approach with descriptive methods and field research. In obtaining data, this research uses library research, observation, interviews and documentation. The results of this study concluded that economic independence at the Nur El Falah Islamic Boarding School, Serang, Banten, was not maximized, around 40 percent running productive waqf. While only relying on cash waqf through a digital system platform (waqf via digital). Meanwhile, at the Fathul Ulum Kwagean Islamic Boarding School in fostering the economic independence of the pesantren by maximizing the pesantren business unit with the pattern of Syirkah and mudharabah and the results are to support the development and development of the pesantren. Keywords: Islamic boarding school, productive waqf, syirkah and mudharabah